Implementatıon Of Dıscovery Learnıng Wıth Gamıfıcatıon Concept To Improve 21st Century Skılls - Zam Zam Jamaludin; Ryan Dwi Puspita (Jurnal Elementaria Edukasia, 2024)
This research is motivated by the difficulties experienced by most students in solving problems in learning, the difficulty of working together because they do not want to share knowledge with each other, and lack of confidence in presenting in front. One way to improve these skills is by implementing discovery learning. However, discovery learning has a weakness in efficiency in managing learning so that it requires gamification as a solution in managing learning. The purpose of this study is to improve 21st century skills in grade IV students of SD Evans Indonesia Kota Bangun so that they can become a foundation of character so that they are ready to face challenges in the 21st century. This research method is carried out qualitatively. The data collection and analysis techniques are carried out using the Miles & Huberman model including (1) Data collection through literature studies and observations; (2) Data reduction in the form of observation tables; (3) Data presentation in the form of scripts; and (4) Drawing conclusions. The results of this study indicate that students can solve problems in learning through critical and creative thinking skills, communicate and collaborate very well and can present confidently in front of the class so that the application of discovery learning with the concept of gamification can improve 21st century skills. These findings indicate that a fun and challenging learning approach can encourage students to become learners to face the challenges of the 21st century.